2012
DOI: 10.1371/journal.pone.0032790
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ecology and Severe Pollen Limitation in the Polychromic Tundra Plant, Parrya nudicaulis (Brassicaceae)

Abstract: Pollen limitation is predicted to be particularly severe in tundra habitats. Numerous reproductive patterns associated with alpine and arctic species, particularly mechanisms associated with reproductive assurance, are suggested to be driven by high levels of pollen limitation. We studied the reproductive ecology of Parrya nudicaulis, a species with relatively large sexual reproductive investment and a wide range of floral pigmentation, in tundra habitats in interior montane Alaska to estimate the degree of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 74 publications
(131 reference statements)
2
37
0
Order By: Relevance
“…The phenomenon that pollinator limitation was more serious in high altitudes than low altitudes has been found in many species of alpine plants (Tate & Simpson, 2004;Arroyo et al, 2006;Zhang et al, 2006;Fulkerson et al, 2012;Zhao & Wang, 2015). Our results revealed that in P. siphonantha plants growing at high altitudes were mainly limited by quality (outcross) pollen rather than by the quantity of pollen deposited.…”
Section: Variations In Pollen Limitation and Mating Systemsupporting
confidence: 54%
“…The phenomenon that pollinator limitation was more serious in high altitudes than low altitudes has been found in many species of alpine plants (Tate & Simpson, 2004;Arroyo et al, 2006;Zhang et al, 2006;Fulkerson et al, 2012;Zhao & Wang, 2015). Our results revealed that in P. siphonantha plants growing at high altitudes were mainly limited by quality (outcross) pollen rather than by the quantity of pollen deposited.…”
Section: Variations In Pollen Limitation and Mating Systemsupporting
confidence: 54%
“…Since the frequency of white individuals is positively correlated with the length of the growing season, we suspect climatic factors (or correlated, non-pollinator selective agents) interacting with the petal color contribute to the maintenance of this polymorphism [13]. We have also detected selection against individuals with lighter colored petals along the Arctic Coastal Plain, but not in interior Alaska where the climate during the growing season is more benign [14].…”
Section: Introductionmentioning
confidence: 75%
“…Acceptance of ovule bet-hedging as deeply engrained in flowering plants would be greatly strengthened by empirical evidence coming from comparisons of ovule number in plant communities differing in levels of pollination stochasticity. In general, alpine and Arctic habitats are characterized by strongly stochastic pollination as evidenced by variable visitation rates, erratic visitation, wide variation in numbers of pollen grains deposited on stigmas, and large differences in seed set per flower (Ai, Zhou, Xu, Wang, & Li, 2013;Bergman et al, 1996;Eriksen, Molau, & Svensson, 1993;Fulkerson, Whittall, & Carlson, 2012;Hocking, 1968;Kasagi & Kudo, 2003;Kudo, Hirao, & Kawai, 2011;Ladinig & Wagner, 2007;Ladinig, Hacker, Neuner, & Wagner, 2013;Lundemo & Totland, 2007;McCall & Primack, 1992;Tiusanen, Hebert, Schmidt, & Roslin, 2016;Torres-Diaz et al, 2007;Totland, 1994Totland, , 1997Tur, Sáez, Traveset, & Aizen, 2016;Waites & Ågren, 2004). Progressively shorter growing seasons with increasing elevation and latitude place further restrictions on pollination and seed set by limiting the amount of time available for flowering and seed maturation (Körner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Alpine areas and the Arctic thus are prime candidates for ovule bet-hedging (Burd et al, 2009). However, although the possibility of ovule oversupply has been mentioned by some authors (Fulkerson et al, 2012;Wagner, Lechleitner, & Hosp, 2016), no study has explicitly tested the ovule bet-hedging hypothesis in these harsh environments for animal pollinators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation